2022
DOI: 10.1007/s10113-022-01998-w
|View full text |Cite
|
Sign up to set email alerts
|

Nature-based solutions for climate change adaptation are not located where they are most needed across the Alps

Abstract: Climate change impacts mountains socio-ecosystems by increasing certain natural disasters and changing Nature's Contributions to People (NCP). Nature-based Solutions (NbS) are increasingly implemented to help local communities adapt to climatic hazards. However, the relevance of their location in relation to those hazards and local NCP has hardly been addressed. In the PORTAL project (Pathways of Transformation in the Alps), we identified and mapped a portfolio of 97 NbS for climate change adaptation in the Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 123 publications
1
6
0
Order By: Relevance
“…The three NbS types are new findings that complement previous classifications of NbS. While some scholars discriminated NbS according to climatic hazards, NCP co-benefits (25,26) or types of intervention (18,69), we found that different interventions, or NbS addressing different climatic hazards, can be implemented by similar decision-making contexts. In other words, different local contexts can achieve transformative adaptation to one climatic hazard.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…The three NbS types are new findings that complement previous classifications of NbS. While some scholars discriminated NbS according to climatic hazards, NCP co-benefits (25,26) or types of intervention (18,69), we found that different interventions, or NbS addressing different climatic hazards, can be implemented by similar decision-making contexts. In other words, different local contexts can achieve transformative adaptation to one climatic hazard.…”
Section: Discussionsupporting
confidence: 78%
“…Study limitations Our study focused on a small number of NbS implemented in the Alps. However, our sample captures the diversity of activities that have been identified to address drought, floods and soil erosion in this region (26,113). Our insights can support NbS amplification in other regions, as we identified common levers and barriers with studies from other socio-ecological systems worldwide (70,114).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations